Investigations of potassium-induced surface treatment of Cu(In,Ga)Se2 (CIGSe) thin film solar cells prepared by two-stage process using elemental selenium - Zheng, X (Elsevier BV, 2020)
10.1016/j.apsusc.2020.146368